The Application of Physical Exercise in Improving the Quality of Dance Movements at the Junior High School Level : english - Maharani, Nabila; Suryandoko, Welly (Solah, 2025)
this study aims to describe the process of physical training in traditional dance extracurricular activities in schools and its positive benefits in the success of students’ movements. The method used is qualitative with data collection techniques through observation, interviews, and documentation. The results of the study show that physical exercise training which includes stretching, balance, breathing, and coordination of head, hand, and foot movements makes a real contribution to improving students’ flexibility, balance, technique, and movement expression. These findings reinforce the importance of integrating physical training in dance coaching in the school environment, especially to improve the quality of movement performance in traditional dance.